Deteksi Lemari Terguling Berbasis IoT dengan Notifikasi Telegram untuk Keselamatan Anak - Nanda Pratama Widya Iswara; Sujono (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Household accidents involving children are often caused by furniture such as cabinets or shelves tipping over after being pushed or climbed on. This condition may result in serious injuries, therefore an early warning system that can quickly detect changes in furniture position is required. This study aimed to design and develop a cabinet or shelf tipping detection system based on the Internet of Things (IoT) with Telegram notifications as an alert medium for parents. The method used included hardware design using the ESP8266 module as the main controller and the MPU6050 sensor to detect tilt angles, as well as software design for data processing and message delivery through the Telegram Bot Application Programming Interface. The system worked by reading tilt angle data on specific axes and comparing them with predefined safety thresholds. When the angle exceeded the threshold, the system automatically sent warning messages to the parents’ smartphones. The test results showed that the system successfully detected dangerous tilt conditions and delivered notifications within a relatively short response time, indicating that it can function as an early warning system to improve child safety in home environments. This system is expected to assist parents in monitoring furniture stability and preventing accidents caused by tipping